Drinking Plain Water Before Having Breakfast Lowers Body Weight in Obese Male Adolescents - Gracia, Vera Viviana Deo; Indarto, Dono; Tamtomo, Didik Gunawan (Jurnal Keperawatan Soedirman, 2018)
ABSTRACTDrinking plain water can increase daily energy expenditure and decrease total energy intake. This study aimed to analyze the effects of drinking plain water before eating steamed rice with high glycemic index (GI) at breakfast, on body weight (BW) and blood glucose level (BGL) in obese male adolescents. Twenty male adolescents aged 15-18 years old and had BMI for age > 85 percentile participated in this randomized control trial study. Ten male students in G1 group drank 250 ml plain water before eating 180 g steamed rice with high GI and 10 male in the other group (G2) drank the same amount of water after eating the same rice for breakfast for 7 days. Paired and independent t tests were used to analyze BW and BGL in both groups with p value < 0.05. Mean BW change in G1 was significantly different from mean BW changes in G2 (p=0.006), whereas mean fasting and 1h after meal BGLs changes of both groups were similar. Drinking water before having breakfast reduces BW in obese male adolescents.ABSTRAKMinum air putih dapat meningkatkan pengeluaran energi harian dan mengurangi total asupan energi. Penelitian ini bertujuan untuk menganalisis pengaruh minum air putih sebelum sarapan nasi kukus dengan indeks glikemik (IG) tinggi terhadap berat badan (BB) dan kadar glukosa darah (KGD) pada remaja putra dengan obesitas. Dua puluh remaja putra berusia 15-18 tahun dan IMT/U > 85 persentil berpartisipasi dalam penelitian randomized control trial study ini. Sepuluh remaja putra kelompok K1 minum 250 ml air putih sebelum sarapan 180 g nasi kukus dengan IG tinggi dan 10 remaja putra kelompok K2 minum air putih dalam jumlah yang sama setelah sarapan nasi yang sama selama 7 hari. Uji t berpasangan dan independen digunakan untuk menganalisis BB dan KGD pada kedua kelompok dengan nilai p <0,05. Rata-rata selisih perubahan BB pada kelompok K1 berbeda secara signifikan daripada rata-rata selisih perubahan BB pada kelompok K2 (p = 0,006) sedangkan rata-rata KGD puasa dan 1 jam posprandial sama pada kedua kelompok. Kesimpulan: Minum air putih sebelum sarapan nasi menurunkan BB pada remaja putra dengan obesitas.